Implementasi direct dan indirect marketing sebagai upaya dalam menarik minat masyarakat menjadi donatur zakat : Studi pada Baitul Maal Hidayatullah Malang - Sarif, Reza (Maliki Interdisciplinary Journal, 2025)
This study discusses the marketing strategy of Baitul Maal Hidayatullah (BMH) Malang in attracting public interest to donate zakat through direct marketing and indirect marketing approaches. This study was motivated by the trend of increasing public awareness of zakat, followed by the strategic role of zakat institutions in managing funds professionally. The study used a qualitative method with data collection through interviews with marketing division staff. The results show that direct marketing is implemented through sending personal messages via WhatsApp and email, with contact segmentation (hot, warm, and cold) to increase message relevance and audience response. Meanwhile, indirect marketing is carried out through the creation of informative articles published online to build awareness and long-term relationships without direct promotion. The combination of these two strategies has proven effective in increasing public participation in the BMH zakat program. This study provides insight for other zakat institutions in designing innovative marketing strategies to increase social impact.